The Effect of Implementation of Management Support Work Environment, Team Work, and Employee Development to Employee Engagement with Employee Motivation as Mediating Variable - Nelson, Alden (MEC-J (Management and Economics Journal), 2021)
Employee engagement is essential for the company's long-term growth and increased profits in an increasingly competitive industry. This study aims to analyze the effect of implementing a management support,Â  work environment, team work, employee development to employee engagement. The research conducted in manufacturing companies in Batam with 396Â  respondents. The data test using SPSS and Smart PLS. The results of the study explained the direct effect variable has significant effect and variable teamwork has very significant effect compare to other independent variables. Indirect influence explains that team work have a significant effect to employee engagement through employee motivation but management support does not significantly influence employee engagement through employee motivation.Â